A coupled polymeric porphyrin complex as a novel cathode for highly stable lithium organic batteries. Issue 40 (14th April 2020) - Yuan, Jingjun; Ren, Bo; Feng, Xin; Gao, Ping; Liu, Enhui; Tan, Songting
Abstract : A polymeric porphyrin as a new cathode exhibits both high reversible capacity and long-term cycling stability for lithium organic batteries. Abstract : A highly conjugated polymeric porphyrin with an ethynyl group is proposed as a new cathode for lithium organic batteries. The electrochemical performance is significantly improved after a simple coupled polymerization, resulting in excellent cycling stability with a capacity retention of 99.2% for 2000 cycles.